Buku Teks PAI dan Pencegahan Bullying di Sekolah Dasar - Qurrata 'Aini; Mokh. Iman Firmansyah (Pendidikan Agama Islam, Fakultas Ilmu Tarbiyah dan Keguruann, IAIN Syekh Nurjati Cirebon, 2024)
While the majority of research to date has been more focused on studying Islamic Religious Education (PAI) models, media and practices in forming students' anti-bullying character, this study is focused on efforts to examine whether PAI material provides adequate accessibility to enable students to have knowledge, understanding, anti-bullying attitude and character. Therefore, the aim of this article is to explore PAI materials in elementary schools and analyze accessibility for the attitudes and character of anti-bullying students in elementary schools. This article uses an exploratory qualitative approach to content analysis design, where PAI books and morals for grades I to VI in elementary schools be the source. This article finds two characters that can prevent bullying behavior in students, namely performance and moral character. Regarding the similarities between the two characters, they both have positive values that can be applied in everyday life, including behaving politely, respecting others, being devoted to parents and teachers, forgiving each other, and loving each other. In this way, students can live in harmony and avoid bullying behavior.